ChemInform Abstract: Trifluoromethoxylation of Arenes: Synthesis of ortho‐Trifluoromethoxylated Aniline Derivatives by OCF3 Migration. Issue 19 (May 2015) - Hojczyk, Katarzyna N.; Feng, Pengju; Zhan, Chengbo; Ngai, Ming‐Yu
Abstract: N‐protected N‐arylhydroxylamines are initially O‐trifluoromethylated prior to a thermally induced migration of the CF3 ‐O‐group from the amino function to the ortho‐position of the attached arene.